The effectiveness of acaricidic drugs based on herbal raw material - Voronova, Nataliya; Horban, Valeriy; Bohatkina, Viktoriia (Ecological Questions, 2021)
Limitation the number of ixodes ticks is one of the most important tasks of modern science and requires the search for new, highly effective and environmentally hazardous acaricides, so our experiment was aimed at identifying acaricidal properties of essential oils and their individual active components in the population of ixodes ticks in Zaporizhzhia region. The study of acaricidal properties of essential oils was performed in the laboratory conditions. Tampons with wool were soaked in various concentrations of 0.5%, 1%, 3%, 5% and 10% aqueous emulsion of essential oils such as Caryophyllus floris aetheroleum and Limonis aetheroleum, and essential oils of Thymus serpyllum L., Рinus sylvestris L., Salvia officinalis L., Mentha x piperita L. and Eucalyptus viminalis Labill. The essential oils had a significant effect on the lifespan of adult ticks. The results showed the acaricidal effect of Thymus serpyllum essential oils. When searching the acaricidal and repellent properties of individual essential oils components thymole, menthol and citral showed the high activity as acaricides. In the same time, eugenol and borneol proved the effectiveness as repellent. Our research schowed that essential oils are promising as alternative methods of controlling the number of Ixodes ticks in areas where there are conditions for infection with tick infections.